AKUMULASI TIMBAL (Pb) DAN KEANEKARAGAMAN JENIS Lichenes DI TAMAN KOTA MEDAN - Chandra, Radiansyah Hadi (BIOLINK (Jurnal Biologi Lingkungan, Industri, Kesehatan), 2015)
This reseach aim of the study is to examine factors affecting the accumulation of lead content (Pb) and other types Lichenes in Medan city park. This study was conducted on March 2010. The research location is determined by using purposive sampling method, in the three parks in the Beringin Park, Ahmad Yani Park, and Bunga Teladan Park. Lichenes species diversity existing in the three parks of Medan, consists of three types of tribes Physciaceae with body type ofÂ  thalus Cructose are Dirinaria Picta, Dirinaria aplanata, and Pixine cocoes. At the parks biggest influence is the Beringin Park motorized pedicab (Betor) with regression equation Y = (-0.059) + 000157x and a private car with a value of Y = (-0.059) + 0.0009428x, at the Ahmad Yani Park is a private car with a value of Y = 0.011 + 0.0001501x, and at the Bunga Teladan Park of motorized pedicab (betor) with a value of Y = (-0.099) + 0.000535x to increment the accumulated content of Pb in the body thalus Lichenes. Accretion physical parameters that affect the accumulation of lead (Pb) in Beringin Park regrasi the temperature with the equation Y = (-0.059) + 0.002x, Ahmad Yani Park of moisture with the value Y = 0.011 + 0.0003243x, and light intensity with the value Y = 0.011 + 0.0009387x, while in Bunga Teladan Park of temperature with the value Y = (-0.099) + 0.005 x, and humidity, with a value of Y = (-0.099) + 0.0001543 x.